What constitutes a fulfilled life? A mixed methods study on lay perspectives across the lifespan - Baumann, Doris; Ruch, Willibald (Frontiers in Psychology, 2022)
Recently, we initiated a new research line on fulfillment in life by developing a conceptual framework and a self-report measure. To enhance conceptual clarity and complement theoretical considerations and empirical findings, we investigated lay conceptions of a fulfilled life in German-speaking participants at different life stages. First, we selected a qualitative approach using an open-ended question asking participants to describe a fulfilled life. Second, for a more comprehensive understanding, quantitative data were collected about the relevance of sources in providing fulfillment and ratings on a fulfilling life in the present and a fulfilled life in retrospect. Qualitative content analysis was used to assess the responses to the open-ended question. One fifth of the data was double coded, and intercoder reliability was high (Kappa = .89). Responses comprised a variety of descriptions, and we grouped them into seven themes, three of which overlapped with the prior conceptualization, namely the core elements of (a) general description, (b) cognitive appraisals, and (c) affective appraisals. Cognitive evaluations related to intrapersonal aspects, particularly having lived life fully, attained personally significant goals, and developed oneself, as well as interpersonal, generative aspects, such as having made a contribution and been able to leave something of value. These categories are mostly in line with what the Fulfilled Life Scale (FLS) measures. Further themes referred to correlates – including (d) sources – and antecedents, including (e) resources, (f) personal characteristics, and (g) quality of life, all considered worthy to be the subject of empirical investigation but which were not included in the conceptual model. Qualitative and quantitative results suggest that individuals derive fulfillment from different sources. Fulfillment from a profession and having a life task was strongly associated with longer-term fulfillment. Only a few age and sex differences were found. The overarching framework developed from the qualitative results can stimulate further investigation. Our findings underscore that a fulfilled life as a distinct construct should be measured directly rather than via a proxy. Insights into the constituents, sources, and antecedents of a fulfilled life can inform practice to promote a life well lived.